2007
DOI: 10.1016/j.cgh.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Cancer Risks in Relatives of Young-Onset Cases: Is Risk the Same Across All First-Degree Relatives?

Abstract: Background and Aims-In the last fifteen years, several single-gene Mendelian disorders have been discovered that may account for some of the familial aggregation detected in large population studies of colorectal cancer (CRC). Mutations in DNA mismatch repair (MMR) genes cause HNPCCLynch Syndrome, the most common of the recognized CRC-predisposition syndromes, in which one major feature is a young age for cancer onset. However, for young onset microsatellite stable( MSS) CRC, the familial risk for CRC is unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 9 publications
4
27
0
2
Order By: Relevance
“…2) consistent with the familial risk of tumors related to hereditary nonpolyposis colorectal cancer which is associated with a young age at onset. [36][37][38][39] We also found high familial aggregation of breast cancer at younger ages consistent with reports of higher prevalence of mutations in the BRCA1/BRCA2 genes in young patients and a high probability of the same gene mutations in their sisters. 40,41 Examining the changing risk with time since the index person's diagnosis, we found the pattern varied by cancer site: for colorectal and breast cancer, the risk profile for siblings was approximately constant for up to 20 years while for melanoma there was evidence of a small decline in risk in the first 5 years, and for prostate cancer a sharp decline.…”
Section: Epidemiologysupporting
confidence: 90%
See 1 more Smart Citation
“…2) consistent with the familial risk of tumors related to hereditary nonpolyposis colorectal cancer which is associated with a young age at onset. [36][37][38][39] We also found high familial aggregation of breast cancer at younger ages consistent with reports of higher prevalence of mutations in the BRCA1/BRCA2 genes in young patients and a high probability of the same gene mutations in their sisters. 40,41 Examining the changing risk with time since the index person's diagnosis, we found the pattern varied by cancer site: for colorectal and breast cancer, the risk profile for siblings was approximately constant for up to 20 years while for melanoma there was evidence of a small decline in risk in the first 5 years, and for prostate cancer a sharp decline.…”
Section: Epidemiologysupporting
confidence: 90%
“…The incidence rates differed by cancer site: for example, at age 60 years, the absolute risk (per 10,000 person years) of colorectal cancer in control siblings was 6.55 (95% CI: 5.86-7.31) compared to 16 (Table 2a). From age-stratified analysis, younger siblings had the highest IRR for colorectal cancer, breast cancer and prostate cancer, but the IRR was highest in 40-50 year old siblings for melanoma, although this was of similar magnitude to the IRR in the youngest siblings (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40). The IRRs for each cancer decreased with age and were relatively stable in older ages.…”
Section: Absolute Risk Of Cancer By Agementioning
confidence: 89%
“…In a codominant model of inheritance, an inherited predisposition to develop sessile serrated adenomas and CRC may be attributable to carriers of one allele, and the more severe phenotype associated with hyperplastic polyposis may be the result of homozygous carriers or a carrier paired with a recessive allele. Studies (35,36) have shown that CRC risk is significantly greater among siblings than for parent-offspring, which is suggestive of recessive inheritance. Interestingly, in a large populationbased study (35), the greatest CRC risk was associated with an affected sibling who had a right-sided colon cancer.…”
Section: Resultsmentioning
confidence: 99%
“…It is higher in people with a stronger family history, such as a history of colorectal cancer or adenomatous polyps in any first-degree relative younger than age 60; or a history of colorectal cancer or adenomatous polyps in two or more first-degree relatives at any age. 25 The reasons for the increased risk are not clear, but it likely due to inherited genes, shared environmental factors, or some combination of these.…”
Section: Family History Of Colorectal Cancer or Adenomatous Polypsmentioning
confidence: 99%